Hierarchical Tubular Structures Grown from the Gel/Liquid Interface. Issue 49 (21st October 2014) - Steenbjerg Ibsen, Casper Jon; Mikladal, Bjørn Fridur; Bjørnholt Jensen, Uffe; Birkedal, Henrik
Abstract Three dimensional hierarchical materials are widespread in nature but are difficult to synthesize by using self‐assembly/organization. Here, we employ a gel–liquid interface to obtain centimeter‐long ∼100 μm diameter tubes with complex mineral wall structures that grow from the interface into solution. The gel, made from gelatin, is loaded with metal chloride salt, whereas the solution is a high pH anion source. Tubes were obtained with a range of cations (Ca2+, Sr2+, Ba2+, Cu2+, and Zn2+) and anions (CO32− and PO43−). The crystalline phases found in the tube walls corresponded to expectations from solution chemistries and phase solubilities. The growth mechanism is found to be akin to that of chemical gardens. The divalent cations modify the strength of the gelatin gel in a manner that involves not only simple electrostatic screening, but also ion‐specific effects. Thus, tubes were not obtained for those ions and/or concentrations that significantly changed the gel's mechanical structure. At high Cu2+ loading, for example, vertical convection bands, not Liesegang bands, were observed in the gels.